DEVELOPMENT OF SELF-EFFICACY SCALE FOR SCIENCE EDUCATION - Dilber POLAT (Fırat University, 2019)
Visuals related to education are indispensable for a country's development level. In order for Turkey to be within developed countries, a number of innovations are needed in education alongside other country dynamics. The key to reaching educational objectives of a country is to raise teachers who have intense beliefs that they can achieve teaching in that country. At this point, the concept of self-efficacy is instrumental. Self-efficacy is one's belief that s/he can achieve a certain task. The self-efficacy perception is a concept incorporated in social learning theory and the main motivational construct behind the in